Modern Crisis Phenomena and Its Impact on the Development of Small and Medium-Sized Enterprises - G. D. Petrova; M. I. Kheyfets (Здоровье мегаполиса)
Introduction. The segment of small and medium-sized enterprises is one of the top priorities for the strategy of economic development of the Russian Federation. Thus, studies on this topic seem to be relevant. The share of small and medium-sized entrepreneurship (SMEs) in the GDP of developed countries ranges from 35 to 65 %, while the share of SMEs in the GDP of the Russian Federation still does not exceed 20 %.The current challenges affecting the economy of the Russian Federation, including the COVID-19 pandemic and the current geopolitical situation, as well as sanctions against the Russian Federation imposed by other countries, have had a significant negative impact on small and medium-sized enterprises.Purpose of the study. The purpose of this study was to review and analyze current crisis phenomena and its impact on the development of importing companies from the SME segment in order to identify key areas requiring the development of new approaches to crisis management.Results and conclusion. Study results show that modern crisis phenomena have had a significant impact on the development of the SME segment, thus forming a completely new market environment. New challenges have affected almost all activity areas of importing companies from the SME segment from the internal management policy (organization of the company's activities and personnel management) to the rules for importing goods, including logistics, calculations, value management, etc.